E-banking and its impact on quality of banking services in Libya: a case of public commercial banks service in Sebha city - Aboazom A. Aboujdiryha, Uones I. Abukhtwah (Journal of Pure & Applied Sciences, 2018)
This study aims at diagnosing the current status of e-banking in Libya and its impact on the quality of banking services by studying the case of five commercial public banks operating in the city of Sabha. The study used a descriptive analytical method as well as questionnaires were distributed to the study society. One of the most important findings of the study is that there is a relationship between e-banking and its four dimensions: information base, research and development, security, marketing strategy and the quality of banking services. The study also shows that the commercial banks in Sabha are still providing banking services under the traditional banking system, as the cash payment, certified instruments, and wire transfers are the only payment tools available within the city of Sabha. In addition to the personal presence to the bank is a crucial to obtain the simplest banking services, which caused many problems and confusion in the daily work, long cue and waiting for long hours to get the simplest banking services. The study recommends that the commercial banks operating in Sabha should review the traditional patterns used to provide banking services and seriously oriented towards modern banking models based on e-banking, especially in the current challenges in Libya including security breakout, lack of liquidity, and frequent interruption of electricity, as e-banking has advantages in providing banking services in 24 hours a day, 7 days a week, and providing safety allowance instead of carrying money.